Surprise soup - Rodman, Mary Ann.; Karas, G. Brian (New York : Viking, 2009)
Kevie, excited by the prospect of being a big brother, helps make a special soup to welcome his mother and new sibling home from the hospital.
Booklist starred.
School Library Journal.
Wilson's Children.
2.1
K-3
Keywords: Bears -- Juvenile fiction; Brothers -- Juvenile fiction; Families -- Juvenile fiction; Soups -- Juvenile fiction; Bears -- Fiction; Brothers -- Fiction; Family life -- Fiction; Soups -- Fiction; Bears -- Fiction; Brothers -- Fiction; Family life -- Fiction; Soups -- Fiction